Evolution of crystal structure and ferroic properties of La-doped BiFeO3 ceramics near the rhombohedral-orthorhombic phase boundary - Karpinsky, D. V.
Bi1-xLaxFeO3 ceramics (0.15 <= x <= 0.2) across the rhombohedral-orthorhombic phase boundary have been studied using X-ray and neutron diffraction, magnetization measurements and piezoresponse force microscopy (PFM). The regions of structural stability of the polar, anti-polar and non-polar phases have been identified depending on the dopant concentration and a temperature and the structural phase diagram has been further clarified. The factors influencing phase transitions (size effects, chemical bonds peculiarities, local chemical inhomogeneities, etc.) have been estimated. PFM measurements testified a maximal piezoelectric response for a compound with the dominant rhombohedral phase in a metastable state. Magnetic properties have been discussed assuming weak ferromagnetic state with a major contribution from the orthorhombic phase. An evolution of structural parameters across the phase boundary decisive for improved ferroelectric and magnetic properties has been analyzed. (C) 2012 Elsevier B. V. All rights reserved.